LEGAL DOMICILE OF THE PARTIES IN A SIMPLE LAWSUIT - Ully, Artha (Walisongo Law Review (Walrev), 2019)
The purpose of this paper is to examine the publication of Perma No. 2 of 2015 concerning Procedures for Settling a Simple Lawsuit. Perma can be seen as one solution to meet the needs of the community for dispute resolution procedures quickly and simply. The substance contained in Perma is to uphold the principle of justice which is simple, fast, and low cost. Therefore, the requirements in a simple lawsuit are limited in nature, where if one of the conditions is not fulfilled, the case cannot be resolved through the Simple Lawsuit Procedure in accordance with Perma No. 2 of 2015. The results of the author's research, the Perma substance is needed to be improved, because the limitation of jurisdiction is only one legal domicile and the use of legal counsel in a simple claim is something that needs to be regulated in more detail, in the future to further encourage the use of a simple claim mechanism as a instrument of applying the principle of justice that is simple, fast, and low cost in Indonesia. The Supreme Court needs to regulate in more detail the role of the attorney in simple lawsuits, such as regulating the right to speak a legal representative and the problem of the absence of the principal in the event that the party is a legal entity; Electronic calling via Sms, whasapp and email can be an alternative used in the calling process, so Perma should regulate in more detail the terms and conditions of the validity of the information technology-based calling. Tujuan penulisan ini adalah  untuk menelaah penerbitan Perma No. 2 Tahun 2015 tentang Tata Cara Penyelesaian Gugatan Sederhana. Perma itu dapat dipandang sebagai salah satu solusi untuk memenuhi kebutuhan masyarakat terhadap prosedur penyelesaian sengketa dengan cepat dan sederhana. Substansi yang terkandung di dalam Perma yaitu menjunjung asas peradilan yang sederhana, cepat, dan berbiaya ringan. Oleh karena ini persyaratan dalam gugatan sederhana bersifat limitatif, di mana bila salah satu syarat tidak dipenuhi, maka perkara tersebut tidak dapat diselesaikan  melalui Prosedur Gugatan Sederhana sesuai PERMA No. 2 Tahun 2015. Hasil penelitian penulis, substansi Perma diperlukan pernyempurnaan, karena pembatasan yurisdiksi hanya pada satu domisili hukum dan penggunaan kuasa hukum dalam gugatan sederhana merupakan hal yang perlu diatur secara lebih rinci, di masa yang akan datang untuk lebih mendorong penggunaan mekanisme gugatan sederhana sebagai instrumen penerapan asas peradilan yang sederhana, cepat, dan berbiaya ringan di Indonesia. Mahkamah Agung perlu mengatur lebih rinci peran kuasa hukum dalam gugatan sederhana, seperti mengatur hak bicara kuasa hukum dan masalah ketidakhadiran prinsipal dalam hal pihak adalah badan hukum; Pemanggilan secara elektronik melalui SMS, WA dan email dapat menjadi alternatif yang digunakan dalam proses pemanggilan, maka PERMA sebaiknya mengatur secara lebih rinci syarat dan ketentuan keabsahan pemanggilan berbasis teknologi informasi tersebut.